Modern and holocene pollen assemblages from Arctic ice caps. - Bourgeois, Jocelyne C. (University of Ottawa (Canada), 2000)
Records of pollen deposition on arctic ice caps are used to infer paleoenvironments of the Holocene and atmospheric circulation patterns in the Arctic. As part of this study, several snow samples were collected over a broad area, over the course of several years, to investigate modern pollen deposition patterns in the Arctic. Pollen assemblages recovered from arctic snow are diverse and consist of tundra and forest types. The results show that pollen percentages and concentrations are related to the density of the regional vegetation and to the distance of the source in more productive regions. In addition, the long-distance transport of tree and shrub pollen permits the identification of regional patterns that might be used to define air mass trajectories in the Arctic. In a more detailed analysis, the seasonal and annual variations in pollen deposition in snow layers were studied on four ice caps, including one in the Russian Arctic. It is shown that the pollen succession in the annual snow layers is related to the flowering periods of arctic and southern plants. The amount of pollen reaching the ice caps varies from year to year. Furthermore the variability in the number of tree and shrub pollen increases with decreasing distance to the treeline. The last section of this study is an interpretation of a Holocene record of pollen distribution in an ice core from the Agassiz Ice Cap, Ellesmere Island. Pollen concentrations, particularly those of tree pollen, were highest in the early Holocene, decreased in the mid-Holocene, and changed relatively rapidly after ca. 3500 years ago. In the early Holocene, the pollen profile parallels the delta 18O and ice-melt records from the same ice core, indicating that the warmest summer temperatures occurred very early in the Holocene. The high concentration of tree pollen in the early Holocene, when large parts of Canada were still ice-covered and forest zones more limited and generally farther away, implies that atmospheric circulation was stronger than at present. The data may be of significant value to comprehensive studies of atmospheric dynamics and vegetation changes.
Keywords: Palynology.